The role of leader favoritism, unfairness, and employability in employee psychological withdrawal behavior - Mohd Shamsudin, Faridahwati (2023)
Given the adverse consequences of destructive leadership at work, we examine leader favoritism prevalent in contemporary organizations. Our study builds on previ ous research on unethical leadership behaviors and extends social exchange theory by assessing whether leader favoritism contributes to employee psychological with drawal behavior at work and whether perceived unfairness explains this link, address ing a gap in the literature on this topic. In addition, we investigate the condition of perceived employability to seek whether the influence of perceived unfairness due to leader favoritism on psychological withdrawal behavior at work is strengthened when employees think they can secure alternative employment elsewhere. The study utilizes a two- wave data collection approach to gather responses from 206 front end customer service employees working in the hospitality and tourism firms in the United Arab Emirates (UAE). The study findings offer empirical support for the proposed mediated moderation model. Specifically, the results demonstrate that leader favorit ism directly, indirectly (via perceived unfairness), and positively influence employee withdrawal behaviors. This influence is stronger among employees who believe they can easily find alternative employment options. Our findings highlight the relevance of incorporating social exchange theory into the unethical leadership behaviors and withdrawal behaviors literature and provide valuable insights for managers into how to mitigate the practice of leader favoritism because of its adverse consequences on employees' work attitudes and behavior.